Regenerating neighbourhoods in partnership - learning from emergent practices. - (:unkn) unknown (My University, 2004)
This report addresses new ways of regenerating deprived urban neighbourhoods in European cities. How can we make these better places to live and work in? We present here - in summary form - practical solutions developed by over 50 practitioners, policy makers and researchers in the ENTRUST network of eight European cities to the challenges faced by people working at the front line of urban regeneration.ENTRUST (Empowering Neighbourhoods through Recourse and Synergies with Trade) is a European network of over 50 practitioners, policy-makers and researchers in eight European cities Berlin, Copenhagen, Dublin, Glasgow, Hamburg, Lisbon, Valetta and Vilnius. It is supported by the European Commission under the Fifth Framework RTD Programme/Key Action 4 'City of Tomorrow and Cultural Heritage'. The network of city teams was generated by Byfornyelse Danmark on request of the City of Copenhagen and Integrated Area Planning in Dublin. ENTRUST followed up and extended previous steps of cooperation in INTERREG IIC (Integrated Urban Planning and Management, 1998-2001). ENTRUST was launched in 2002. A major focus of the network was to involve partnerships in, and for the betterment of deprived neighbourhoods whilst producing and making use of the transnational knowledge base. Its main aims are raising awareness of, and facilitating new approaches to urban regeneration.
Keywords: Stadtentwicklungsplanung; Stadtteil; Problemraum; Stadterneuerung; Stadtquartier; Segregation; Förderungsprogramm; Bewohnerbeteiligung; Fallstudie; Planungsbeispiel; Benachteiligter Stadtteil; Soziale Stadt; Handlungsfeld; Aufwertung; EU-Förderung